(untitled) (Studies in ELT and Applied Linguistics, 2025)
Kshetteli, a recently identified Tibeto-Burman language, is spoken by only four elderly people of the three villages, viz., Jhusku, Salli and Khatti, in the Darchula district of Nepal. Within Sustainable Use Model, this paper with some linguistic and sociolinguistic background briefly describes some processes of assessing the present level of language use and vitality of the Kshetteli language and suggests some effective community based activities after assigning an EGIDS level for achieving a desired sustainable language use in the language. By analyzing both quantitative and qualitative data, this paper has revealed some typologically interesting phonological, morphological, syntactic and lexical features of the language. Besides, it has presented some sociolinguistic features including ethnolinguistic situation, language attitude and multilingualism. Generally, Kshetteli has been found to be a critically endangered language. This language has turned into a heritage language which retains only an identificational function with 9 (Dormant) EGIDS level. Thus, this language, which maintains sustainable identity, has to be uplifted from 9 to EGIDS level 8a (Nearly Extinct) for awakening the language and fulfilling community’s desire to achieve sustainable orality by devising different activities for the transmission of internal life-crucial knowledge to the younger generations. Such activities may include developing corpus and language documentation technology, teaching the language in schools, forming a culture group and convincing the local policy makers to frame a multilingual language policy for uplifting the heritage language like Kshetteli. However, in order to transmit external life-crucial knowledge, at present, English has to be taught and learned by the community members as a large body of external life-crucial knowledge is primarily embodied in English.